Kinerja Marshall Immersion pada Asphalt Concrete Wearing Course (AC-WC) dengan Limbah Bottom Ash Sebagai Substitusi Agregat Halus - Rifaidi, Muhammad; Abdillah, Nuryasin; Abrar, Aidil (SLUMP TeS : Jurnal Teknik Sipil, 2024)
The use of solid fuel in the form of coal as an energy source produces bottom ash and fly ash waste, which can cause environmental pollution. This research aims to examine the effect of using bottom ash as a substitute for fine aggregate on stability, flow, voids in the mixture (VIM), voids in mineral aggregate (VMA), ), voids filled with asphalt (VFA) and the Marshall Quotient of asphalt concrete mixtures. This research was carried out in the Dumai College of Technology laboratory, using asphalt levels of 6%, 8% and 10% with each level representing 4 samples of test objects. From the research it was found that the use of bottom ash waste as a substitute for fine aggregate in the asphalt mixture affected the Flow, VIM and VFA values which were not included in the specifications determined by Bina Marga Revision 3 of 2010.